The thermal contact resistance of a steel-ceramic interface with oxide intermediates. Issue 1 (1st January 2020) - Silvonen, Jussi; Levänen, Erkki; Uusitalo, Mikko
Abstract: Metal structures covered by refractories are widely employed in high temperature processes such as incineration and metal production. The thermal resistance in refractories used in high temperature processes is associated with different phases, phase boundaries and porosity in the refractory and with the thermal contact resistance between the refractory and the metal interface. Here, a light flash method was used to evaluate the thermal contact resistance of the ceramic/steel interface at temperatures of 25, 100, 200, 300 and 400 °C. The material combinations studied were a commonly-used reference ceramic, Pyroceram 9606, and pressure vessel steel with oxidizing treatment at 450 and 650 °C for 50 h. Thermal resistance at a ceramic/steel interface increased significantly when a porous oxide layer was formed on the steel surface. The thermal contact resistance of the interface varied from 0.1 to 0.4 × 10 −3 m 2 K/W, depending on the temperature and the oxidization of the steel sample.